2021
DOI: 10.1016/s2665-9913(21)00222-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibody development after COVID-19 vaccination in patients with autoimmune diseases in the Netherlands: a substudy of data from two prospective cohort studies

Abstract: Background Data are scarce on immunogenicity of COVID-19 vaccines in patients with autoimmune diseases, who are often treated with immunosuppressive drugs. We aimed to investigate the effect of different immunosuppressive drugs on antibody development after COVID-19 vaccination in patients with autoimmune diseases. Methods In this study, we used serum samples collected from patients with autoimmune diseases and healthy controls who were included in two ongoing prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
175
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(202 citation statements)
references
References 28 publications
23
175
2
2
Order By: Relevance
“… 23 Although not statistically significant, the data from our limited sample size also suggest numerically lower levels of anti-spike IgG in immunosuppressed patients, compared with controls. Similar trends were identified in other cohorts of patients with immune-mediated inflammatory diseases, 9 , 19 , 24 and these findings have raised questions about whether dose modification of methotrexate or temporary discontinuation could enhance immune responses to COVID-19 vaccines. As this strategy was shown to be successful in promoting immunogenicity to the influenza vaccine, 25 a 2 week interruption in methotrexate after the COVID-19 booster is currently under investigation in a multicentre, randomised controlled trial.…”
Section: Discussionsupporting
confidence: 76%
“… 23 Although not statistically significant, the data from our limited sample size also suggest numerically lower levels of anti-spike IgG in immunosuppressed patients, compared with controls. Similar trends were identified in other cohorts of patients with immune-mediated inflammatory diseases, 9 , 19 , 24 and these findings have raised questions about whether dose modification of methotrexate or temporary discontinuation could enhance immune responses to COVID-19 vaccines. As this strategy was shown to be successful in promoting immunogenicity to the influenza vaccine, 25 a 2 week interruption in methotrexate after the COVID-19 booster is currently under investigation in a multicentre, randomised controlled trial.…”
Section: Discussionsupporting
confidence: 76%
“…Izmirly et al showed that fully vaccinated SLE patients (n=90) produced significantly lower IgG antibodies against SARS-CoV-2 spike receptor binding domain (RBD) than healthy controls (HCs) (n=20) [14]. Boekel et al reported that among participants without previous SARS-CoV-2 infection, seroconversion rates after first COVID-19 vaccination in patients with AIIRDs (n=432) were lower than HCs (n=210), an effect that was mainly driven by those treated with MTX or B cell-depletion therapies; however, differences in seroconversion rates were similar across autoimmune disease types examined [15]. Similarly, Ammitzbøll et al observed a higher seroconversion rate following BNT162b2 vaccine in SLE (n=73) than RA (n=64) patients, but the difference was not statistically significant after adjusting for RTX treatment [16].…”
Section: Efficacy Of Covid-19 Vaccines In Patients With Systemic Lupusmentioning
confidence: 99%
“…[1][2][3][4][5][6] Indeed, serum levels of SARS-CoV-2 immunoglobulin (Ig)G following SARS-CoV-2 vaccinations and infections are reduced in anti-CD20 treated pwMS. [7][8][9] Nevertheless, in addition to antibody levels, protection from infection, and especially from severe courses of coronavirus disease-19 (COVID- 19), may depend on neutralizing capacity and avidity of anti-SARS-CoV-2 antibodies as well as on induction of SARS-CoV-2 specific T cells. [10][11][12] However, data on anti-SARS-CoV-2 antibody neutralization capacity and avidity in anti-CD20 treated pwMS are scarce.…”
Section: Introductionmentioning
confidence: 99%